SAT0361 Trabecular bone score in osteogenesis imperfecta. is it useful?. (12th June 2018) - Florez, H.; Muxi, A.; Gonzalez, E.; Monegal, A.; Guañabens, N.; Peris, P.
Abstract : Background: The trabecular Bone Score (TBS) is a novel gray-level textural analysis measurement that can be applied to DXA images to estimate trabecular microarchitecture and has been shown to be related to direct measures of bone microarchitecture and fracture risk. Osteogenesis impefecta (OI) is a congenital bone disease characterised by a low bone mineral density (BMD) and poor bone quality and strength. The usefulness of TBS in OI has been scarcely evaluated. Objectives: To analyse the clinical usefulness of TBS determination in patients with OI and its relation with anthropometric and clinical features (especially concerning skeletal fractures and BMD results). Methods: Twenty-four patients (18 F:6 M) with OI with a mean age of 38±15 years 19–63 attending a Metabolic Bone Disease Unit were included. The clinical reports of the patients were reviewed, with especial attention to the clinical features (weight, height and body mass index [BMI]), previous fractures, disease severity, associated mutations and treatments received. Lumbar spine (LS), total hip (TH), and femoral neck (FN) BMD were measured using DXA equipment (Lunar) in all patients. TBS was analysed in LS, and the results were classified in three categories 1 : TBS >1.310 (normal), TBS 1.230–1.310 (partially degraded microarchitecture), TBS <1.230 (degraded microarchitecture). TBS values were compared with a healthy control group of similar age and gender. Results: 5/24 patients (21%) had a degraded microarchitecture, 4 (17%) a partially degraded microarchitecture and 15 (63%) normal TBS. All patients with TBS <1230 were over 40 years old. 21/24 patients had a previous history of multiple fractures. Regarding BMD, 54% of the patients had osteoporosis, 42% osteopenia and one had normal values. Most patients had a mutation in the COL1A1 gene (63%). A correlation was observed between TBS and age (r=−0.5, p=0.006) and LS BMD (r=0.5, p=0.014), showing a trend to significance with BMI (r=−0.4, p=0.058). No significant differences were observed on comparing TBS in patients and controls (1.321 vs. 1.391, p=N .S.). Conclusions: TBS measurement does not seem to be useful for evaluating bone strength in patients with OI. Despite most patients presenting a history of multiple fractures, only 21% showed degraded microarchitecture with TBS. Reference: [1] McCloskey EV, Odén A, Harvey NC, et al. J Bone Miner Res2016;31:940–8. Disclosure of Interest: None declared